2021
DOI: 10.36456/jet.v6.n01.2021.3512
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy: Text Credibility on Critical Reading Material

Abstract: With the onset of the digital era, the classroom's teaching and learning process has also shifted. The use of technology makes it easy for lecturers and students to access various information and references on the internet. However, not all of the information and concerns come from reliable and credible sources, so it is necessary to select and sort out the references used. This research's background determines students' ability to find and utilize and evaluate the credibility of information to be used in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…This mixed-up information sometimes provides trusted and untrusted information (Haider, 2008). Students need to be equipped with skills of digital literacy thus they are able to choose information on the internet that is credible and trustworthy (Leliana et al, 2021;Maureen et al, 2018). Previous study found that there were still many students who were not aware of the credibility of the information on the internet (Caverly et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This mixed-up information sometimes provides trusted and untrusted information (Haider, 2008). Students need to be equipped with skills of digital literacy thus they are able to choose information on the internet that is credible and trustworthy (Leliana et al, 2021;Maureen et al, 2018). Previous study found that there were still many students who were not aware of the credibility of the information on the internet (Caverly et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in technology, particularly in telecommunications and computing, have resulted in significant improvements in accessibility. With affordable mobile, tablet and computer devices and fast internet connections, individuals can communicate and access information on social media through computer applications (Hikmah, 2019;Leliana et al, 2021). The next effect is the social addiction that arises from using these applications.…”
Section: Introductionmentioning
confidence: 99%